2013
DOI: 10.3348/kjr.2013.14.4.692
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon of the Uncommon: Malignant Perivascular Epithelioid Cell Tumor of the Lung

Abstract: A perivascular epithelioid cell (PEC) tumor is a rare mesenchymal tumor characterized by abundant cytoplasmic Periodic acid-Schiff positive glycogen (also called sugar tumor or clear cell tumor of the lung for this characteristic) and is mostly benign. We report a case of a 63-year-old man who presented with an enlarging mass on chest radiograph. After a thorough workup, diagnosis of malignant pulmonary PEC tumor with lung to lung metastases was established. Herein, the difficulties of diagnosis and management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Other reports suggested that arteriovenous hypervascularity in contrast-enhanced CT and MR images is a feature of PEComas (9, 11). Lim et al (2) recently reported imaging findings for a pulmonary malignant PEComa, which were characterized by well-defined, multiple round nodules exhibiting heterogeneous and intense enhancement (the solid portion was associated with strong enhancement, i.e., 115 HU on post-contrast images). Similar manifestations were also noted in our case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other reports suggested that arteriovenous hypervascularity in contrast-enhanced CT and MR images is a feature of PEComas (9, 11). Lim et al (2) recently reported imaging findings for a pulmonary malignant PEComa, which were characterized by well-defined, multiple round nodules exhibiting heterogeneous and intense enhancement (the solid portion was associated with strong enhancement, i.e., 115 HU on post-contrast images). Similar manifestations were also noted in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Two large, well-defined, multi-loculated ovarian masses were detected, accompanying multiple septal and peripheral enhancing solid portions that typically showed intense enhancement in the portal phase and slight delayed washout. Although the majority of previously reported PEComas appear to behave in a benign fashion, a malignant course with local recurrence and distant metastasis has also been reported (2, 4, 12). Malignant PEComas are associated with two or more of the following worrisome features: high mitotic rate (> 1/50 high-power fields), atypical mitotic figures, marked pleomorphism and nuclear atypia, hypercellularity, infiltrative growth pattern, large tumor size (> 5 cm), and the presence of necrosis or vascular invasion (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] The biological behavior of this neoplasm is traditionally considered benign; however, malignant CCTL has also been discovered and reported in several other literatures. [9–12] Certain clinicopathologic features such as a diameter >2.5 cm, the presence of symptoms, and extensive necrosis or abundant mitoses visible under an optical microscope are correlated with more aggressive behavior. [1315] Surgical resection is an acceptable curative approach for CCTL, as the tumor's benign behavior is not invariable, and chemotherapy or radiotherapy has not demonstrated significant benefits for malignant CCTL.…”
Section: Discussionmentioning
confidence: 99%
“…CCSTs are mainly benign and manifest as peripheral and smooth-edged quasi-circular nodules, without cavities or calcification, which may be markedly enhanced (11,12). Malignant CCSTs are manifested as multi-nodules or masses, with occasional calcification and metastasis to the liver, adrenal gland or brain (13). LAM manifest on high-resolution CT as quasi-circular and almost wall-less cysts in diffuse distribution, likely accompanied by pneumothorax, pleural effusion or chylothorax, and occasionally with small AML and retroperitoneal lymphangioma in the kidneys (14).…”
Section: Discussionmentioning
confidence: 99%